2014
DOI: 10.1627/jpi.57.18
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Nickel and Vanadium from Heavy Oils Using Supercritical Water

Abstract: Heavy oils require substantial cracking in order to be economically refined to produce usable products. One major problem affecting the economics of refining heavy oils is the metal compounds contained in many of these oils which poison the catalyst used to crack the oil. Demetallization methods include physical, chemical, electrochemical, catalytic and supercritical water (SCW) techniques. Few of these methods are viable and/or efficient for the demetallization of heavy oil. This paper discusses the SCW based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 56 publications
2
19
0
Order By: Relevance
“…Zhao et al [44,45] reported that the upgrading of heavy oil in SCW could significantly lower the Ni and V content in the upgraded products. Mandal et al [97,[104][105][106] systematically studied the non-catalytic demetalization of three model porphyrinic compounds (nickel-5,10,15,20-tetraphenylporphine, nickel etioporphyrin, and vanadyl etioporphyrin) in SCW. In these experiments, they analyzed the effect of temperature and pressure on the demetalization of porphyrinic compounds.…”
Section: Removal Of Nickel and Vanadiummentioning
confidence: 99%
“…Zhao et al [44,45] reported that the upgrading of heavy oil in SCW could significantly lower the Ni and V content in the upgraded products. Mandal et al [97,[104][105][106] systematically studied the non-catalytic demetalization of three model porphyrinic compounds (nickel-5,10,15,20-tetraphenylporphine, nickel etioporphyrin, and vanadyl etioporphyrin) in SCW. In these experiments, they analyzed the effect of temperature and pressure on the demetalization of porphyrinic compounds.…”
Section: Removal Of Nickel and Vanadiummentioning
confidence: 99%
“…It produces vanadium pentoxide when it burns during the combustion process [4,5]. Vanadium pentoxide is a toxic material and is harmful to the environment.…”
Section: Heavy Metal Removal Processesmentioning
confidence: 99%
“…Moreover, continuous hydrothermal systems ofer the ability to carry out synthesis in a high-throughput mode, enabling the discovery of new materials [75]. Furthermore, SCW can remove heavy metals from metalloporphyrin compounds efectively and eiciently in an environmentally friendly way [76]. Thus, the sc-CO 2 and the SCW have atracted tremendous interest among academia and industry in this modern era as a green process.…”
Section: History Of Scfmentioning
confidence: 99%